2022
DOI: 10.1016/j.ijregi.2022.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with asymptomatic and symptomatic COVID-19 admitted to a tertiary referral centre in the Philippines

Abstract: Objectives We aimed to describe the clinical profile and outcomes of hospitalized patients with COVID-19 across the spectrum of disease activity. Methods This was a retrospective study of adult patients with confirmed COVID-19 infection admitted in a referral hospital. Descriptive statistics, tests for trend, Kaplan-Meier curve and log-rank test were used to compare characteristics and outcomes across disease activity. Results Of 1500 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Our study showed that high D-dimer, high LDH, low ALC, and low albumin levels were associated with disease progression, while elevated D-dimer and LDH were associated with in-hospital mortality. These findings are consistent with other international and local reports on COVID-19 (11,(42)(43)(44)(45). The finding of high D-dimer also provided evidence for SARS-CoV-2 infection as a hypercoagulable state (46), which further supports the use of prophylactic anticoagulation among patients with moderate to severe COVID-19.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study showed that high D-dimer, high LDH, low ALC, and low albumin levels were associated with disease progression, while elevated D-dimer and LDH were associated with in-hospital mortality. These findings are consistent with other international and local reports on COVID-19 (11,(42)(43)(44)(45). The finding of high D-dimer also provided evidence for SARS-CoV-2 infection as a hypercoagulable state (46), which further supports the use of prophylactic anticoagulation among patients with moderate to severe COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…The cohort in this study consists predominantly of patients with severe to critical COVID-19 disease (69%). This is higher compared to published data from the same institution (48.9%) and another tertiary referral center in Metro Manila (54.1%) even after excluding mild and asymptomatic patients (11,35). The recorded mortality rate of 18% closely approximates the data from both reports, 15.1% in UP-PGH (11) and 20.8% in San Lazaro Hospital (35).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Since the model assumes that the infected cases among students are asymptomatic [18, 19, 20, 21] and undetected [22], hence, there are no isolation for infected and exposed students. We assume that the student population is fixed with no deaths.…”
Section: Methodsmentioning
confidence: 99%
“…Further psychosocial distress is likely to impact those directly affected by COVID-19 by either contracting the disease or having to take care of a family member who has been infected with COVID-19. Furthermore, COVID-19 severely affects the elderly, who require more attention and care [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%